THE EFFECT OF KEPOK BANANA HEART NUGGETS (NGET-JAPOK) AGAINST BREAST MILK PRODUCTION (ASI) - Sri Heryani; Arifah Septiane Mukti; Siti Rohmah (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2022)
Mother's Milk (ASI) is the best source of food for babies, because breast milk has many ingredients that are very beneficial for babies. One of the benefits obtained is as immunity in the body. So that the achievement of exclusive breastfeeding will reduce the infant mortality rate. (Umboh et al., 2013). Data from the World Health Organization (WHO) in 2020 stated that the rate of exclusive breastfeeding was 44% during the 2015-2020 period, this is also in line with a survey conducted by Lambantorium in 2018 which stated that the coverage of exclusive breastfeeding in Indonesia was still very minimal at 27 ,6%. (Fk and Andalas, 2017). Efforts that can be made in increasing the coverage of breast milk production are by paying attention to the nutrition of nursing mothers, where one of the efforts that can be done is to utilize plants as the fulfilment of nutrition for breastfeeding mothers. The plant that can be used is the kapok banana heart. Where this kepok banana heart is a type of plant that is easily obtained and the content contained in the kapok banana heart is useful in increasing breast milk production. (Pratiwi et al., 2016). The purpose of this study is to improve the status of the coverage of successful exclusive breastfeeding and to provide the latest study materials related to methods of increasing breast milk production. The method used in this research is to use pre test and post test designs. In this study a sample of one intervention group Based on statistical tests, it was found that the production of breast milk before the intervention was only 5.4, while after it increased to 9.9. The correlation between the two variables is 1.580, the difference in the average value of increasing breast milk production with a sig value of 0.000.